The Influence Of Red Onion Extract (Allium cepa L.), Coconut Water (Cocos nucifera L.) Towards Growth Of Sandalwood (Santalum album L.) - Lindi Djawa, Barnadus Nggahu; Arpiwi, Ni Luh; Sudirga, Sang Ketut (Metamorfosa: Journal of Biological Sciences, 2020)
The purpose of this study was to determine the effect of onion extract, coconut water and scarification on sandalwood growth. This study used a complete randomized design with six treatments and three replications in each unit of the experiment. The parameters measured in this study were the percentage of seedlings growing, plant height, number of leaves, leaf length, and leaf width. Data analysis using ANOVA with a test of 5% if there is a real difference in one of the factors followed by the Duncan Multiple Range Test (DMRT) at the 5% test level using SPSS statistical analysis. The results showed the treatment of shallot extract and scarification methods gave good results on the growth of sandalwood seedlings by 70% and the combined scarification treatment with young coconut water gave the best results on the growth of sandalwood plants. For this reason, the writer recommends that sandalwood farmers use onion extract or scarification to increase the percentage of seedlings growing while to stimulate the growth of sandalwood plants using a combination of scarification with young coconut water.   Keyword : onion, coconut water, scarification